Mountain-river runoff components and their role in the seasonal development of desert-oases in northwest China. (November 2015) - Matin, Mir A.; Bourque, Charles P.-A.
Abstract: The paper examines the role of mountain runoff in the seasonal growth of oasis vegetation in the hyper-arid region of northwest China. Central to this examination is the development of a simple hydrologic model that relates hydrologic inflows and outflows estimated from remote sensing data (e.g., evapotranspiration, precipitation, snow accumulation, and snowmelt) to the calculation of runoff over a ten-year period (2000–2009). Modeled runoff is shown to reproduce the seasonal trends in hydrometric data fairly well, yielding R 2 's of 0.75 and 0.66 for stations in the upper reaches of the Shiyang and Hei River systems. Greater than 90% of the runoff from the Qilian Mountains to the oases occurs during the May–September period. Considerable discrepancy between modeled and observed runoff exists in the lower reaches of the rivers, where significant amounts of river water (>45%) are routinely extracted for cropland irrigation. Along the river systems, where water extraction and inflow of glacial meltwater are minor, model calculations replicate observed water yields much more closely. Analysis of seasonal trends in the contribution of snowmelt and rainfall to the return flow, reveals snowmelt as having the greatest influence in initiating the oasis growing period during the March-to-May period of each year. Highlights: Monthly river runoff is modeled from remote-sensing data and distributed modeling. The model gives spatially-distributed estimates of water yield and soil moisture. Modeled runoff is validated against actual in-river water yields. Results are best where irrigation and glacial meltwater are unimportant. Significant runoff is diverted for irrigation in oases closest to the mountains.